2006
DOI: 10.1007/s00285-006-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of CFSE proliferation assay

Abstract: CFSE based tracking of the lymphocyte proliferation using flow cytometry is a powerful experimental technique in immunology allowing for the tracing of labelled cell populations over time in terms of the number of divisions cells undergone. Interpretation and understanding of such population data can be greatly improved through the use of mathematical modelling. We apply a heterogeneous linear compartmental model, described by a system of ordinary differential equations similar to those proposed by Kendall. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 20 publications
4
76
0
Order By: Relevance
“…IL-2 only moderately affects the cell interdivision time, but reducing the IL-2 concentration increases the degree of stochasticity of the cell division. Interestingly, a recent study has also found dependence of the rate of cell death and proliferation on the division number for lymphocytes stimulated with PMA in vitro (21).…”
Section: Discussionmentioning
confidence: 93%
“…IL-2 only moderately affects the cell interdivision time, but reducing the IL-2 concentration increases the degree of stochasticity of the cell division. Interestingly, a recent study has also found dependence of the rate of cell death and proliferation on the division number for lymphocytes stimulated with PMA in vitro (21).…”
Section: Discussionmentioning
confidence: 93%
“…Alternatively, one can restrict the use of this probe to cell types which are quiescent, or in which cell division is unlikely to begin before dye equilibration has occurred. More recently, dynamic approaches to modeling the proliferation of CFSE stained cells have been investigated, making use of sophisticated statistical and calculus based formulae to assist in the interpretation of experimental data (Deenick et al, 2003;Hawkins et al, 2007;Liu et al, 2006;Luzyanina et al, 2007). Mathematical correction may also account for continued, slow rates of dye loss (after 24-48 hours) in populations where an unstimulated, non-dividing control sample is not possible (Matera et al, 2004;Ubezio et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, mathematical models adopting this mechanical description (so-called "transition probability" or "compartment" models) remain popular and form the basis of many studies of lymphocyte and cancer kinetics in vitro and in vivo today (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%